Implementasi Ability Grouping Kelas Unggul MTs Negeri 2 Bandar Lampung - ayu, sovia mas; Junaidah, Junaidah (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2020)
Abstract The practice of grouping the ability to give many problems to students and cause injustice in education. Studies of western scholars reveal the negative side of ability grouping related to inequality, labeling and low student self-esteem. This study aims to analyze the perspective of the ability grouping concept for principals and teachers, identify the implementation of ability grouping at MTs 2 Bandar Lampung, determine the effect of ability grouping on student academic achievement, and determine the effect of ability grouping on teaching and learning in the classroom. This study used a qualitative approach to the type of case study, with the research location in the superior class of MTs N 2 Bandar Lampung. The results showed that the principal and teachers had understood the basic concept of implementing ability grouping, the applied ability grouping had followed the rules and technical guidelines issued by the central and regional religious ministries, there were differences in both academic and non-academic achievement between superior and regular class students, and there are differences in aspects of the learning process applied by the teachers.Keywords: Implementation, Ability Grouping, Superior Class Abstrak Abstrak Praktik pengelompokan kemampuan memberikan banyak masalah kepada siswa dan menyebabkan ketidakadilan dalam pendidikan. Studi dari para sarjana barat mengungkapkan sisi negatif dari pengelompokan kemampuan terkait dengan ketidak setaraan, pelabelan dan harga diri siswa yang rendah. Penelitian ini bertujuan untuk menganalisis perspektif konsep ability grouping kepala sekolah dan guru, mengidentifikasi implementasi ability grouping di MTs 2 Bandar Lampung, mengetahui pengaruh ability grouping pada prestasi akademik siswa, dan mengetahui pengaruh ability grouping  pada pengajaran dan pembelajaran di kelas. Penelitian ini menggunakan pendekatan kualitatif jenis studi kasus, dengan lokasi penelitian di kelas unggul MTsN 2 Bandar Lampung. Hasil penelitian menunjukkan bahwa kepala sekolah dan guru telah memahami konsep dasar pelaksanaan ability grouping, ability grouping yang diterapkan telah mengikut iaturan dan petunjuk teknis yang dikeluarkan kementerian agama pusat dan wilayah, terdapat perbedaan baik prestosi akademik dan non akademik antara siswa kelas unggul dan regular, dan terdapa tperbedaan pada aspek proses pembelajaran yang diterapkan para guru.  Kata kunci :Implementasi, Ability Grouping, Kelas Unggul